Citrinin Monomer and Dimer Derivatives with Antibacterial and Cytotoxic Activities Isolated from the Deep Sea-Derived Fungus Penicillium citrinum NLG-S01-P1 - Weiyi Wang; Yanyan Liao; Beibei Zhang; Maolin Gao; Wenqian Ke; Fang Li; Zongze Shao (Marine Drugs, 2019)
Two previously unreported citrinin dimer derivatives, penicitol D (1) and 1-epi-citrinin H1 (2), were isolated from the culture of a deep sea-derived fungus Penicillium citrinum NLG-S01-P1, together with 11 biogenetic related compounds (3–13). A plausible biogenetic pathway for compounds 2–4 was proposed. Their structures, including absolute configurations, were established through analysis of extensive spectroscopic data and time-dependent density functional theory (TD-DFT) ECD calculations. Compounds 1 and 2 showed antibacterial activities against methicillin-resistant Staphylococcus aureus (MRSA). Compounds 5 and 10 displayed relatively stronger activities than the other compounds against Vibrio vulnificus and Vibrio campbellii. Compound 1 showed the most potent cytotoxic activity towards the HeLa cell.